2004
DOI: 10.1103/physrevb.69.140502
|View full text |Cite
|
Sign up to set email alerts
|

Determining the current polarization in Al/Co nanostructured point contacts

Abstract: We present a study of the Andreev reflections in superconductor/ferromagnet nanostructured point contacts. The experimental data are analyzed in the frame of a model with two spin-dependent transmission coefficients for the majority and minority charge carriers in the ferromagnet. This model consistently describes the whole set of conductance measurements as a function of voltage, temperature, and magnetic field. The ensemble of our results shows that the degree of spin polarization of the current can be unamb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 24 publications
7
90
0
Order By: Relevance
“…Second, in the present paper, we consider the case that the area of the contacts of FM1 and FM2 with SC are several nanometers and thus the proximity effect can be neglected. 33,47,48,49 IV. CONCLUSION We present a theory of the crossed Andreev reflection in structures consisting of a superconductor with two ferromagnetic leads.…”
Section: 56mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in the present paper, we consider the case that the area of the contacts of FM1 and FM2 with SC are several nanometers and thus the proximity effect can be neglected. 33,47,48,49 IV. CONCLUSION We present a theory of the crossed Andreev reflection in structures consisting of a superconductor with two ferromagnetic leads.…”
Section: 56mentioning
confidence: 99%
“…Throughout this paper, we neglect the impurity scattering in SC and the proximity effect near the interfaces. 33,47,48,49,50,51 The solution of the BdG equation in the SC region is given by…”
Section: Model and Formulationmentioning
confidence: 99%
“…Recent experimental studies on equilibrium properties of superconductorferromagnet (SF) interfaces have shown that the local density of states (LDOS) on the superconducting side is strongly affected by the pair breaking effect of the ferromagnetic exchange field [1], and on the ferromagnetic side an oscillatory behavior of the LDOS due to the exchange splitting of the spin sub-bands has been observed [2]. Transport properties of SF point contacts [3,4,5] and FSF planar junctions [6] show a suppression of spin-polarized current injection into the superconductor, and in SFS Josephson junctions [7,8,9], a π-state with a spontaneous equilibrium Josephson current is observed. In this work, we report on spin-dependent transport properties of the superconducting condensate on length scales comparable to the coherence length.…”
mentioning
confidence: 99%
“…Tunneling between superconductors is more complicated since Andreev tunneling may happen multiple times before the electron-hole pairs may overcome the barrier of Andreev reflection [21]. This phenomenon of multiple Andreev reflection is well-known and is accompanied by the usual Josephson current which is an AC voltage whose frequency is determined by the voltage applied across the junction [22] [23] [24].…”
Section: General Theory Of Transport In Superconducting Heterostructuresmentioning
confidence: 99%